2017
DOI: 10.4103/jnrp.jnrp_470_16
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Vision Loss without Ophthalmoplegia as a Rare Complication of Spinal Surgery

Abstract: Postoperative visual loss is an extremely rare complication of nonocular surgery. The most common causes are ischemic optic neuropathy, central retinal artery occlusion, and cerebral ischemia. Acute visual loss after spinal surgery is even rarer. The most important risk factors are long-lasting operations, massive bleedings, fluid overload, hypotension, hypothermia, coagulation disorders, direct trauma, embolism, long-term external ocular pressure, and anemia. Here, we present a case of a 54-year-old male who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Eye injuries and vision loss are extremely rare complications of spinal surgery. [ 49 ] The incidence of visual loss after spinal surgery ranges from 0.028% to 0.2%, with scoliosis correction as the primary surgery. [ 50 ] At the end of the last century, Qiuxu Wang et al [ 51 ] reviewed more than 30 spinal surgery cases complicated by visual impairment and found that vision loss after spinal surgery was rare for complex reasons.…”
Section: Resultsmentioning
confidence: 99%
“…Eye injuries and vision loss are extremely rare complications of spinal surgery. [ 49 ] The incidence of visual loss after spinal surgery ranges from 0.028% to 0.2%, with scoliosis correction as the primary surgery. [ 50 ] At the end of the last century, Qiuxu Wang et al [ 51 ] reviewed more than 30 spinal surgery cases complicated by visual impairment and found that vision loss after spinal surgery was rare for complex reasons.…”
Section: Resultsmentioning
confidence: 99%